Economic Valuation of Marina Beach, Bantaeng Regency - Ramlan, Asrul Rahadi; Amri, Andi; Tahang, Hamzah; Amiluddin, Amiluddin; Hasani, M. Chasyim (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2021)
This study aims to determine the factors that influence the frequency of tourist visits and to determine the economic value of Marina Beach based on the analysis of travel costs using the Travel cost method. This research was carried out at Marina Beach, Bantaeng Regency from February to March 2021 with a sample of 38 people. The research location was chosen purposively with the consideration that Marina Beach is one of the tourism objects whose exact economic value is not known based on the Travel Cost Method, while the sampling is by non-random sampling or non-random sampling/non-probability sampling. Analysis of the data used is multiple linear regression and analysis of economic value based on travel costs. Factors that have a significant influence on the intensity of visits at Marina Beach are the attractiveness of the beach, the location of the beach. While the factors that do not have a significant effect on the intensity of visits at Marina Beach are travel costs, facilities, accessibility, distance from houses, and the level of cleanliness of Marina Beach attractions. Meanwhile, based on the calculation results, it is known that the consumer surplus based on the individual travel cost method (Individual Travel Cost) is a minimum income of Rp. 42,570.65.- per individual per year, and then the economic value of the Marina Beach tourist attraction is Rp. 1,393,484,222 -/year.